Composite coils : compliant in-vivo tissue fixation device - Shah, Ankur Harish (2019)
Surgical adhesives are an attractive alternative to traditional mechanical tissue fixation methods of sutures and staples. Ease of application, biocompatibility, enhanced functionality (drug delivery) are known advantages, but weak adhesion strength in the wet environment and lack of tissue compliant behavior still pose a challenge. In order to address these issues, non-aqueous bioadhesive based on blends of polyamidoamine (PAMAM) dendrimer, conjugated with 4-[3-(trifluoromethyl)-3H-diazirin-3-yl] benzyl bromide (PDz) and liquid polyethylene glycol (PEG 400) has been developed. PEG 400 is a biocompatible solvent which reduces the viscosity of PDz dendrimer without incorporating aqueous solvents or plasticizers, allowing application by syringe or spray. Upon UV activation, diazirine-generated reactive intermediates (Carbenes) lead to intermolecular dendrimer crosslinking forming a dendrimer dominant network. The properties of the crosslinked matrix are tissue compliant, with anisotropic material properties dependent on the PEG 400 weight %, UV dose, pressure, and uncured adhesive thickness. The hygroscopic PDz /PEG 400 blend was hypothesized to absorb water at the tissue interface, leading to high interfacial adhesion, however porous matrices led to cohesive failure. The hydrophilic nature of the polyether backbone (PEG 400) shields cationic PAMAM dendrimers within the cured bioadhesive, displaying significantly less platelet activation than neat PDz or PLGA thin films. Addition of longer PEG chain in the binary adhesive blends provides additional sites of carbene insertion. This improves the mechanical property of the adhesive blends and reduces the dependency on carbene crosslinker. The improvement in the mechanical properties is achieved at the cost of viscosity, limiting tertiary adhesive’s ability to be syringed. The improvement in mechanical properties positively influences the lap shear bioadhesion strength of tertiary adhesive blends by 50-100%. Carbene generation can be increased through high-intensity UVA laser, mitigating the low absorption coefficient (~266 M-1 cm-1) of 4-[3-(trifluoromethyl)-3H-diazirine-3-yl. The heat generated due to high-intensity UVA laser is dissipated by changing the mode from continuous to pulse irradiation. Reducing the energy per pulse transmits low energy and the liquid adhesive acts as a sink to dissipate the thermal energy generated per pulse. Finally, a composite coil architecture is implemented to exploit the carbene precursor adhesive’s unique material properties towards new physiological applications for lumens and blood vessels.